The influence of dust on the image of solar panel and its operation in Libya - A. A. Albagoush; A. B. Abuauba; A. B. Kupriyanov (Системный анализ и прикладная информатика)
The Libyan state, which created the strategic plan for renewable energy 2013–2030, which strives to encourage initiatives aimed at achieving sustainability, is one of the developing nations vying to gain from solar energy in the sector of electrical energy. The agreement to build a 500-MW solar power project made this plan quite evident. The primary barrier to the best possible use of solar energy is pollution, specifically the buildup of dust and bird droppings on solar panels. The efficiency of power generation from solar panels is significantly affected by dust accumulated on them. As a result of the research, quantitative indicators of the impact of dust on photovoltaic systems in Libya were determined and images of the solar panel were obtained with different densities of dust on its surface. The field experiments show that with the increase in dust density, the short-circuit current, open-circuit voltage, and output power of the PV both decrease. The dust with a density of 40 g/m2 can reduce the maximum power of the PV more than on 20 %. The resulting images of the solar panel can be used to assess the degree of dust in automated systems for solar panels cleaning.